Stress and Mental Flexibility in Autism Spectrum Disorders - Stone, PhD, William S.; Iguchi, PhD, Lisa (North American Journal of Medicine and Science, 2013)
Cognitive deficits are well-established core features in autism spectrum disorders (ASD). In this paper, we review representative studies on cognitive flexibility, which is one type of neuropsychological weakness that is often related to repetitive and restricted clinical symptoms in ASD. We also review effects of stress in both typically developing individuals and in individuals with ASD, to show the importance of this factor in modulating relationships between cognitive inflexibility and clinical symptoms related reflecting inflexibility, such as repetitive and restricted behaviors. Finally, we present three case vignettes involving higher functioning individuals to illustrate some of these relationships in individuals, and to suggest the utility of clinical interventions. [N A J Med Sci. 2013;6(3):145-153. DOI: 10.7156/najms.2013.0603145]